Implementation of RFID Technology for the Differentiation of Loyalty Programs - (:unkn) unknown (My University, 2010)
The aim of our study is to show areas of overlap between customer relationship management and the latest radio frequency identification technology. Radio frequency identification has been used in many different industries, mainly for logistics reasons. We believe that it could serve as a customer relationship management tool as well. Here we discuss a model for the retail sector and explain win-win strategies for customers, suppliers, and store management. © Taylor & Francis Group, LLC.
Keywords: Customer relationship management; Customer security; Loyalty; RFID; Shopping mall